Fuzzy Logic in Drone Control - Stijepović, Anja; Sredovic, Una (Bánki Közlemények, 2024)
In this paper, we examine altitude and attitude stabilization of an unmanned aerial vehicle (UAV) using Fuzzy Logic. There are numerous types of UAVs, but the model analyzed in this paper is designed for a quadrotor micro aerial vehicles with mass no greater than 0,1 kg. A fuzzy logic controller with two inputs (errors and derivative errors) and a fuzzy output is designed in order to stabilize the roll, pitch and yaw angles and thealtitude of a drone with four rotors. Since MATLAB is a well developed and commonly used platform by mathematicians and engineers, it was used for building the Fuzzy model. After the creation of appropriate membership functions and a 3x3 table of if-then rules, centroid method was used for the outputs defuzzification and the Mamdani model was tested in Simulink. In addition, a slight perturbation was applied to observe the robustness of this controller during hovering. The model showed a good and stabilized flight control scheme for a quadrotor, even if it is affected by perturbation.